Predictive Factors of Successful Spinal Cord Stimulation in Patients with Chronic Pain: A Retrospective Cohort Study - Yongjae Yoo; Hyungsang Roh; Jee Youn Moon; Eun Joo Choi; Francis Sahngun Nahm; Pyung Bok Lee (Brain Sciences)
Background: Spinal cord stimulation (SCS) is applied for managing chronic intractable pain, but the factors predicting its effectiveness have not been extensively researched. Our study aimed to identify clinical variables that can predict the outcome of SCS. Methods: The electronic medical records of patients who received SCS for chronic intractable pain at two large tertiary teaching institutions in South Korea from 2008 to 2022 were reviewed. A successful outcome was characterized by attaining at least a 50% reduction in pain on the numerical rating scale (NRS) assessed at 6 months. Multivariable analysis was used to investigate the correlation between outcomes of SCS and clinical variables. Results: Of the 213 patients, 108 (50.7%) experienced successful outcomes at 6 months after SCS implantation. At 6 months, both the positive and negative outcome groups had significantly lower NRS pain scores than at baseline. Multivariable analysis revealed that male gender (p = 0.023) was an independent predictor of positive SCS outcomes; conversely, longer pain duration (p = 0.011) was a negative predictor. No significant adverse events associated with SCS were observed throughout the six-month follow-up duration. Conclusions: SCS could be an effective treatment for chronic intractable pain, including complex regional pain syndrome (CRPS) and persistent spinal pain syndrome (PSPS). More successful outcomes may be expected in male patients with a shorter duration of pain. Additional research is required to enhance patient selection processes and to identify clinical characteristics that contribute to improved long-term outcomes.